miR-124 controls male reproductive success in Drosophila. - Weng, R.; Chin, J.S.; Yew, J.Y.; Bushati, N.; Cohen, S.M. (eLife, 2013)
Many aspects of social behavior are controlled by sex-specific pheromones. Gender-appropriate production of the sexually dimorphic transcription factors doublesex and fruitless controls sexual differentiation and sexual behavior. miR-124 mutant males exhibited increased male-male courtship and reduced reproductive success with females. Females showed a strong preference for wild-type males over miR-124 mutant males when given a choice of mates. These effects were traced to aberrant pheromone production. We identified the sex-specific splicing factor transformer as a functionally significant target of miR-124 in this context, suggesting a role for miR-124 in the control of male sexual differentiation and behavior, by limiting inappropriate expression of the female form of transformer. miR-124 is required to ensure fidelity of gender-appropriate pheromone production in males. Use of a microRNA provides a secondary means of controlling the cascade of sex-specific splicing events that controls sexual differentiation in Drosophila. DOI:http://dx.doi.org/10.7554/eLife.00640.001.